2014
DOI: 10.1161/circresaha.114.304951
|View full text |Cite
|
Sign up to set email alerts
|

Lack in Treatment Options for Virus-Induced Inflammatory Cardiomyopathy

Abstract: Downloaded from Van Linthout et al iPSCs and Virus-Induced Inflammatory Cardiomyopathy 541of human iPS-CM and CVB3 copy number in endomyocardial biopsies of corresponding patients are desired. As such, iPS-CM might have a prognostic value, only in relation to endomyocardial biopsies, the diagnostic gold standard. 24 It should also be recognized that via using iPS-CM as antiviral drug platform, only 1 aspect of the viral pathogenesis, that is, the direct cytotoxic effect of CVB3 in cardiomyocytes, is taken into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The disease progression of dilated cardiomyopathy (DCM) is highly diverse because of its aetiological and pathophysiological heterogeneity . Recent clinical and experimental evidence has suggested that immune activation and the consequential inflammatory response in the myocardium may be involved in the process of deteriorating cardiac function, providing a rationale for immunosuppressive therapy in patients with virus‐negative inflammatory cardiomyopathy . Some of the clinical investigations showed a favourable outcome resulting from immunosuppression, in particular for patients selected on the basis of their immunohistochemical histology .…”
Section: Introductionmentioning
confidence: 99%
“…The disease progression of dilated cardiomyopathy (DCM) is highly diverse because of its aetiological and pathophysiological heterogeneity . Recent clinical and experimental evidence has suggested that immune activation and the consequential inflammatory response in the myocardium may be involved in the process of deteriorating cardiac function, providing a rationale for immunosuppressive therapy in patients with virus‐negative inflammatory cardiomyopathy . Some of the clinical investigations showed a favourable outcome resulting from immunosuppression, in particular for patients selected on the basis of their immunohistochemical histology .…”
Section: Introductionmentioning
confidence: 99%
“…Global immunosuppressive interventions with corticosteroids or calcineurin-inhibitors applied during viral persistence phases failed because of an exacerbation of the virus and have been shown to be limited in efficacy during the later phase of the disease as early damages were not reversible. Similarly, interventions with immunoglobulin were ineffective, and antiviral approaches with IFN are still a matter of debate (8,9). Myocarditis remains a major challenge in modern cardiology and underscores the need to explore innovative therapeutic options and specific immunomodulatory interventions that allow a sufficient antiviral defense with a balanced cytokine response that prevents hyperactive inflammatory toxicity.…”
mentioning
confidence: 99%
“…Parvovirus B19 is implicated as a pathogen in the majority of chronic myocarditis cases . However, direct evidence showing a direct causal relationship between B19V cardiac presence and myocarditis is still missing, as well as therapies for B19V‐associated inflammatory cardiomyopathy …”
Section: Discussionmentioning
confidence: 99%
“…3 However, direct evidence showing a direct causal relationship between B19V cardiac presence and myocarditis is still missing, as well as therapies for B19V-associated inflammatory cardiomyopathy. 19 The strongest risk factor for impaired outcome in chronic myocarditis and inflammatory cardiomyopathy is the Figure 5 In situ tissue typing of endomyocardial biopsies in parvovirus B19-positive myocarditis patients before (mRNA+) and after telbivudine treatment (mRNAÀ) via imaging mass spectrometry. (A) Probabilistic latent semantic analysis could distinguish the protein signatures of the B19V mRNA+ (red) and B19V mRNAÀ (blue) patients (Patients 3 and 4 of Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation